P131 CT emphysema score, dynamic hyperinflation and ventilatory efficiency during exercise in patients with COPD. (2nd December 2011) - Elia, D; Sverzellati, N; Tzani, P; Aiello, M; Vecchio, V; Marangio, E; Chetta, A
Abstract : Background: Volumetric CT scan is used for evaluating the severity of emphysema in COPD patients. The aim of this study was to ascertain whether volumetric CT scan of emphysema may provide information on dynamic hyperinflation and ventilatory efficiency during exercise in COPD patients. Methods: We studied 20 patients (5 F; age 67 yrs ±9; BMI 26 kg/m 2 ±4) with COPD. All patients performed baseline lung function test, chest CT scan and symptom-limited cardiopulmonary exercise test. Dynamic hyperinflation and ventilatory efficiency were expressed as the end-expiratory lung volume (EELV, in l) at peak exercise and as the slope of the relationship between minute ventilation (l/min) and carbon dioxide production (l/min) during exercise (VE/VCO2 ). Oxygen uptake (VO2, % pred), dyspnoea and leg fatigue perception (VAS in mm/workload in watts) at peak exercise were also measured. Results: In all patients, a wide range of airflow obstruction was found (FEV1 /VC range: 31%–68%). The volumetric CT scan score mean value of emphysema was 32.4%±8.6 (range 15–50%). We found a correlation between CT scan score and VE/VCO2 (r= 0.511, p=0.02), peak exercise EELV (r= 0.521, p=0.03), and peak VO2 (% pred) (r=− 0.617, p=0.004). Furthermore, the volumetric CT scan score was related to dyspnoea (r= 0.458, p=0.04) and leg fatigue perception (r= 0.566, p=0.009). Conclusions: Our study shows that the presence of emphysema, as assessed by volumetric CT scan, is associated to dynamic hyperinflation and poor ventilatory efficiency during exercise. Additionally, in our patients a reduced aerobic capacity and an increase in dyspnoea and leg fatigue on exertion were associated to high CT score.